Prospective Clinical, Virologic, and Immunologic Assessment of COVID-19 in Transplant Recipients. Issue 10 (October 2021) - Marinelli, Tina; Ferreira, Victor H.; Ierullo, Matthew; Ku, Terrance; Lilly, Les; Kim, S. Joseph; Schiff, Jeffrey; Sidhu, Aman; McDonald, Michael; Hosseini-Moghaddam, Seyed M.; Husain, Shahid; Rotstein, Coleman; et al.
Abstract : Background: Several studies have described the clinical features of COVID-19 in solid-organ transplant recipients. However, many have been retrospective or limited to more severe cases (hospitalized) and have not routinely included serial virological sampling (especially in outpatients) and immunologic assessment. Methods: Transplant patients diagnosed with COVID-19 based on a respiratory sample PCR were prospectively followed up to 90 d. Patients provided consent for convalescent serum samples and serial nasopharyngeal swabs for SARS-CoV-2 antibody (antinucleoprotein and anti-RBD) and viral load, respectively. Results: In the 161 SOT recipients diagnosed with COVID-19, the spectrum of disease ranged from asymptomatic infection (4.3%) to hospitalization (60.6%), supplemental oxygen requirement (43.1%), mechanical ventilation (22.7%), and death (15.6%). Increasing age (OR, 1.031; 95% CI, 1.001-1.062; P  = 0.046) and ≥2 comorbid conditions (OR, 3.690; 95% CI, 1.418-9.615; P  = 0.007) were associated with the need for supplemental oxygen. Allograft rejection was uncommon (3.7%) despite immunosuppression modification. Antibody response at ≥14 d postsymptoms onset was present in 90% (anti-RBD) and 76.7% (anti-NP) with waning of anti-NP titers and stability of anti-RBD over time. Median duration of nasopharyngeal positivity was 10.0 d (IQR, 5.5–18.0) and shedding beyond 30 d was observed in 6.7% of patients. The development of antibody did not have an impact on viral shedding. Conclusions: This study demonstrates the spectrum of COVID-19 illness in transplant patients. Risk factors for severe disease are identified. The majority form antibody by 2 wk with differential stability over time. Prolonged viral shedding was observed in a minority of patients. Reduction of immunosuppression was a safe strategy. Abstract : Supplemental Digital Content is available in the text.